A New Approach to Motorcycle Theft Prevention System Based on Arduino Uno - Wenda, Alex (Politeknik Ganesha Medan, 2022)
The high rate of motorcycle theft was reportedly caused by the negligence of the owner of the motorcycle itself, including forgetting to double lock and leave the key on the motorcycle. This research offers a new approach to prevent motorcycle theft by designing an automatic double lock system through ignition keys, buzzer reminders for left keys, and coordinator points using GPS to track the position of a motorcycle. Automatic dual locks are designed using a solenoid that locks the front and rear disc brakes automatically when the ignition is in the lock position. The buzzer is activated by using a crossbeam sensor consisting of infrared and photodiode mounted on the ignition key slot and seat lock slot which will sound when the user leaves the key in one of the key slots. The Ublox Neo-6m GPS module is used to determine the coordinates of the motorcycle's position if the motorcycle has been stolen. The test results show that the system can work well. User satisfaction testing shows that respondents agree that the system that has been designed has ease of use, is simple and very useful, seen from the average score of usability factor 4.18, simplicity 4.32 and interactivity 4.38 from a scale of 5.